2010
DOI: 10.1007/s00223-010-9379-7
|View full text |Cite
|
Sign up to set email alerts
|

NSAID Exposure and Risk of Nonunion: A Meta-Analysis of Case–Control and Cohort Studies

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs) are frequently used for postoperative pain control. However, concerns regarding the potential deleterious effects of NSAIDs on bone healing have compelled many physicians to avoid NSAIDs in patients with healing fractures, osteotomies, and fusions. We systematically reviewed and analyzed the best clinical evidence regarding the effects of NSAID exposure on bone healing. Medline, Embase, and Cochrane electronic databases were searched for prospective and retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
2
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(110 citation statements)
references
References 64 publications
0
93
2
5
Order By: Relevance
“…The debate is ongoing, but it has recently been demonstrated that ketorolac did not predispose to pseudoarthrosis in an adolescent idiopathic scoliosis surgical population [23]. Likewise, Dodwell et al [24] reviewed NSAID for postoperative pain treatment in seven high-quality retrospective studies in spine surgery and did not find an increased risk of pseudoarthrosis from shortterm NSAID use during a 12-month follow-up period. On the other hand, NSAIDs have demonstrated significant analgesic properties with reduced need of opioids followed by reduced levels of PONV [25].…”
Section: Discussionmentioning
confidence: 99%
“…The debate is ongoing, but it has recently been demonstrated that ketorolac did not predispose to pseudoarthrosis in an adolescent idiopathic scoliosis surgical population [23]. Likewise, Dodwell et al [24] reviewed NSAID for postoperative pain treatment in seven high-quality retrospective studies in spine surgery and did not find an increased risk of pseudoarthrosis from shortterm NSAID use during a 12-month follow-up period. On the other hand, NSAIDs have demonstrated significant analgesic properties with reduced need of opioids followed by reduced levels of PONV [25].…”
Section: Discussionmentioning
confidence: 99%
“…Pro [32] NSAID use at admission Pro [13,27] Con [17,35] NSAID use at discharge Pro [13,27] Con [17,35] Opioid use at admission Pro [12] Opioid use at discharge Pro [12] Human immunodeficiency virus Pro [24] Con [20] Hepatitis C None Diabetes Pro [13,21,27] ASA score Pro [16] Smoking status Pro [13,21,31,36] Con [29,35] Alcohol use Pro [10,13,21] AO classification Pro [30] Con [2,22] ISS score Pro [30] TRISS score Pro [30] ICU days None * Pro articles support a correlation between nonunion and the variable; Con articles show that the variable has no correlation with nonunion; GSW = gunshot wound; NSAID = nonsteroidal anti-inflammatory drug; ASA = American Society of Anesthesiologists; AO = Arbeitsgemeinschaft für Osteosynthesefragen; ISS = Injury Severity Score; TRISS = Trauma and Injury Severity Score; ICU = intensive care unit.…”
Section: Compartment Syndromementioning
confidence: 99%
“…Hareket sırasında ağrının olmaması kemiğin iyileştiğinin belirtisidir. Deneysel hayvan çalışmalarında non streoid anti inflamatuvar ilaçların stres kırığının iyileşmesini geciktirdiği gösterilmiştir (13). Bifosfonat kullanımının etkinliği randomize kontrollü çalışmalar ile desteklenememiştir.…”
Section: Discussionunclassified